Penghambatan Ekstrak Daun Kremah (Alternanthera sessilis) Terhadap Enzim α-amilase secara In-Vitro - Wirasti Wirasti; Titi Lestari; Isyti'aroh Isyti'aroh (Pharmacon: Jurnal Farmasi Indonesia, 2021)
An important treatment for type 2 diabetes is controlling blood glucose levels. α-amylase enzyme in the body plays a role in breaking down carbohydrates into starch. Control of the amylase enzyme is needed in diabetes cases Kremah plant (Alternanthera sessillis) is a plant whose leaves can be used to lower blood glucose levels because it contains secondary metabolites, one of which is flavonoids which can inhibit the α-amylase enzyme. The purpose of this study was to determine the activity and inhibition value of kremah leaves against the α-amylase enzyme. The method used in this research is the enzymatic reaction by measuring the intensity of the color using UV-Vis spectrophotometry. The IC50 value obtained by α-amylase enzyme inhibition was 101.89±7,21 μg / ml while the IC50 acarbose value was 127.17±4,42 μg / ml. These results indicate that kremah leaf extract has activity (hyperglycemia) by inhibiting complex carbohydrate hydrolyzing enzymes such as the α-inhibition enzyme α-Amylase which is good compared to acarbose because the IC50 value of the extract is smaller, so that the leaves of kremah has inhibiting of the α-amylase enzyme.